Randomized controlled trial of an applied behavior analytic intervention for food selectivity in children with autism spectrum disorder. Issue 4 (23rd October 2019) - Peterson, Kathryn M.; Piazza, Cathleen C.; Ibañez, Vivian F.; Fisher, Wayne W.
Abstract : Food selectivity is a common problem for children with autism spectrum disorder (ASD; Schreck, Williams, & Smith, 2004). Behavior‐analytic interventions have the most empirical support for feeding disorders (Sharp, Jaquess, Morton, & Miles, 2011). However, there are no randomized controlled trials that have evaluated its effects with a well‐defined cohort of children with ASD. In the current investigation, we randomly assigned 6 young children with ASD and food selectivity to either an applied behavior analytic intervention or a wait‐list control. We used a crossover randomized controlled trial to evaluate the effects of a multicomponent applied behavior analytic intervention on independent acceptance and mouth clean of 16 novel foods. We subsequently exposed the wait‐list control group to the intervention. We also evaluated the effects of the intervention on individual participants with single‐case designs. The percentage of independent acceptance and mouth clean increased for the applied behavior analytic intervention group, but not for the wait‐list control group until we implemented the intervention.